Perceptions, Attitudes, and AI Adoption Readiness: A Study of Madrasah Ibtidaiyah Teachers in Polewali Mandar, Indonesia - Eli Meivawati; Husnul Khatimah; Rhischa Assabet Shilla (Universitas Sulawesi Barat, 2025)
This study investigates the factors influencing artificial intelligence (AI) adoption readiness among Madrasah Ibtidaiyah (Islamic Elementary School) teachers in Polewali Mandar, Indonesia. Employing a quantitative approach with a cross-sectional survey design, the research examined the relationships between teachers' perceptions of AI benefits (PB), teachers’ attitudes toward AI (TA), and their readiness to adopt AI technologies (AR). Data were collected from 45 teachers selected through purposive sampling based on specific criteria including minimum teaching experience and basic digital technology knowledge. The research instrument consisted of a questionnaire with a 4-point Likert scale measuring the three main variables. Data analysis was performed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings revealed strong support for all three hypotheses: teachers' perceptions of AI benefits significantly influenced their attitudes toward AI (path coefficient = 0.914), teachers' perceptions directly affected their AI adoption readiness (path coefficient = 0.603), and teachers' attitudes positively influenced their adoption readiness (path coefficient = 0.389). The model demonstrated exceptional explanatory power with R-square values of 0.942 for AI adoption readiness and 0.836 for teachers' attitudes toward AI. The SRMR value of 0.075 indicated adequate model fit. These results suggest that while positive attitudes contribute to adoption readiness, the perception of tangible benefits appears to be the more influential factor in teachers' decisions to embrace AI technology. This research provides an empirical foundation for educational stakeholders to design effective AI implementation strategies in Islamic elementary schools by prioritizing demonstrations of tangible technology benefits as the key factor in enhancing teacher adoption readiness.